Role of Growth Regulators and Plant Media on Growth and Yields of Mint - Sulandjari Sulandjari; Bambang Pujiasmanto; Supriyono Supriyono; Puji Harsono; Nurin Adyanisa Fajrin (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2024)
There is a significant industrial demand for products produced by the mint plant (Mentha piperita L.), yet Indonesia cannot meet all of that need. One of the efforts to increase mint plant production is using manure and atonic growth regulators in the right concentration. The method used was a Factorial Randomized Complete Block Design (RCBD) with two factors. The first factor was the composition of the planting media (soil: husk charcoal, soil: husk charcoal; cow manure, soil: husk charcoal: goat manure, soil: husk charcoal: chicken manure, with a ratio of 1: each: 1:1). The second factor was the atonic concentration (0, 1, 2, 3 mL.L-1). The results showed that using chicken manure gave the best results for growth and yield. Atonic administration with a concentration of 2.05 mL.L-1 gave optimum results on the fresh weight of roots, and a concentration of 2,06 mL.L-1 gave optimum results on the dry weight of roots. The combination of the two treatments did not significantly affect the observed variables.